Patients’ and caregivers’ perception of multidimensional and palliative care in amyotrophic lateral sclerosis – protocol of a German multicentre study - Linse, Katharina; Weber, Constanze; Reilich, Peter; Schöberl, Florian; Boentert, Matthias; Petri, Susanne; Rödiger, Annekathrin; Posa, Andreas; Otto, Markus; Wolf, Joachim; Zeller, Daniel; Brunkhorst, Robert; et al. (Neurological Research and Practice, 2024)
Introduction: Amyotrophic lateral sclerosis (ALS) is an inevitably fatal condition that leads to a progressive loss of physical functioning, which results in a high psychosocial burden and organizational challenges related to medical care. Multidimensional and multiprofessional care is advised to meet the complex needs of patients and their families. Many healthcare systems, including Germany, may not be able to meet these needs because non-medical services such as psychological support or social counselling are not regularly included in the care of patients with ALS (pwALS). Specialised neuropalliative care is not routinely implemented nor widely available. Caregivers of pwALS are also highly burdened, but there is still a lack of support services for them. Methods: This project aims to assess the perceptions and satisfaction with ALS care in Germany in pwALS and their caregivers. This will be achieved by means of a cross-sectional, multicentre survey. The examination will assess, to which extend the patients’ needs in the six domains of physical, psychological, social, spiritual, practical and informational are being met by current care structures. This assessment will be linked to mental well-being, subjective quality of life, attitudes toward life-sustaining measures and physician-assisted suicide, and caregiver burden. The study aims to recruit 500 participants from nationwide ALS centres in order to draw comprehensive conclusions for Germany. A total of 29 centres, mostly acquired via the clinical and scientific German Network for Motor Neuron Diseases (MND-NET), will take part in the project, 25 of which have already started recruitment. Perspective: It is intended to provide data-based starting points on how current practice of care in Germany is perceived pwALS and their caregivers and how it can be improved according to their needs. Planning and initiation of the study has been completed. Trial registration: The study is registered at ClinicalTrails.gov; NCT06418646
CRIS-Team Scopus Importer:2024-07-19
Keywords: Amyotrophic lateral sclerosis; Caregiver burden; Motor neuron disease; Palliative care; Psychosocial care; Quality of care